1988
DOI: 10.1007/bf00293628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some chelating agents on the uptake and distribution of 203Hg2+ in the brown trout (Salmo trutta): studies on ethyland isopropylxanthate, diethyl- and diisopropyldithiophosphate, dimethyl- and diethyldithiocarbamate and pyridinethione

Abstract: Brown trout, Salmo trutta, were exposed to water containing 0.1 microgram/l 203Hg2+, alone or with potassium ethylxanthate (PEX), sodium isopropylxanthate (SIX), sodium diethyldithiophosphate (SEP), sodium diisopropyldithiophosphate (SIP), sodium dimethyldithiocarbamate (SMC), sodium diethyldithiocarbamate (SEC) or sodium pyridinethione (SPyr), respectively. After 1 week the uptake and distribution of the 203Hg2+ in the fish were examined by gamma spectrometry. SIX, SIP, SMC, SEC and SPyr induced 2-3 times hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Also, various carbamate-based pesticides including Thiram, the tetramethyl analogue of TTD, enhance intestinal metal uptake and brain deposition of Ni. 51 The enhancing effect of dithiocarbamates on intestinal uptake and brain deposition of Cd is directly related to their lipophilicity; thus, more hydrophilic derivatives of DDC enhanced the intestinal uptake of Cd less efficiently than did DDC, and the degree of enhancement correlated positively with the octanol-water partitioning coefficient. 52 As opposed to these effects of DDC and TTD on metal biokinetics, orally administered chelating agents forming hydrophilic metal complexes may efficiently reduce intestinal metal uptake and local toxicity at early times after oral intoxication, thereby improving prognosis.…”
Section: Chemical-biological Principles For In Vivo Chelationmentioning
confidence: 99%
“…Also, various carbamate-based pesticides including Thiram, the tetramethyl analogue of TTD, enhance intestinal metal uptake and brain deposition of Ni. 51 The enhancing effect of dithiocarbamates on intestinal uptake and brain deposition of Cd is directly related to their lipophilicity; thus, more hydrophilic derivatives of DDC enhanced the intestinal uptake of Cd less efficiently than did DDC, and the degree of enhancement correlated positively with the octanol-water partitioning coefficient. 52 As opposed to these effects of DDC and TTD on metal biokinetics, orally administered chelating agents forming hydrophilic metal complexes may efficiently reduce intestinal metal uptake and local toxicity at early times after oral intoxication, thereby improving prognosis.…”
Section: Chemical-biological Principles For In Vivo Chelationmentioning
confidence: 99%
“…Considering the environmental compartments through which Hg is transferred, aquatic ecosystems are very susceptible to MeHg contamination, as they host active populations of Hg methylating bacteria (Fitzgerald et al, 2007). Uptake and accumulation studies of inorganic mercury in fishes have described the relatively slow absorption and low bioavailability of these metals from water or food and the importance of both administrative routes in determining the accumulation of this metal (Olson et al, 1973;Williams and Giesy, 1978;Huckabee et al, 1979;Stary et al, 1981;Norrgren et al, 1985;Borg et al, 1988;Harrison and Klaverkamp, 1989;Glynn, 1991). The disposition of inorganic mercury in fishes has been characterized after water, oral, and intraperitoneal administration, with the pattern of tissue distribution varying depending on the administrative route.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sodium dimethyldithiocarbamate and sodium diethyldithiocarbamate promoted a 2to 78-fold increase of uptake of all these metals, potassium ethylxanthate increased by 3.9 and 5.9 times the uptake of CH,Hg(lI) and Pb(II), respectively, but did not affect uptake of Hg(I1) and Ni(II), while sodium diethyldithiophosphate promoted a 2. I -fold increase of CH,Hg(II) uptake but did not affect uptake of Hg(I1) and Pb(I1) (Borg et al 1988;Gottofrey et al 1988a & b;Gottofrey & Tjalve 1991;Tjalve & Gottofrey 1991). The way these substances affect the uptake of metals by the trout has been attributed to the relative liposolubility and stability of their chelate-metal complexes (Tjalve & Gottofrey 1991).…”
Section: Discussionmentioning
confidence: 94%
“…We are currently studying the effects of several substances belonging to these groups of compounds on the uptake and distribution of various trace metals in fish. We showed that they have a marked capability to enhance the uptake of Cd(II), Ni(II), Hg(II), CH,Hg(II) and Pb(I1) by the brown trout Salmo trutta which could lead to increased metal concentrations in target organs, like brain (Borg et al 1988;Gottofrey et al 1988a & b;Gottofrey & Tjalve 1991;Tjalve & Gottofrey 1991). Among metals not yet studied in detail, manganese is a major cation found in natural freshwater at concentrations ranging from < I to 40 pg.1-I (Langlois et al 1983), and up to hundreds of pg.1-I in acidic waters (Stokes et al 1988).…”
mentioning
confidence: 85%